Puccini's Turandot - Adami, Giuseppe, 1878-1946 (Opera classics library., 2002)
Turandot, considered by many Puccini's magnum opus, is an incredible operatic masterpiece, a remarkable blend of heroic grandeur, exoticism, and powerful romantic and poignant sentimentalism.